2015
DOI: 10.1007/s10113-015-0806-1
|View full text |Cite
|
Sign up to set email alerts
|

Water supply and water allocation strategy in the arid US West: evidence from the Eastern Snake River Plain Aquifer

Abstract: This article analyzes how irrigating farmers change their micro-level water allocation in response to water supply variations under institutional water constraints and project the irrigation percentage and farm income under future climate scenarios. We use a highly-detailed data sample of irrigation status, water rights, water supply and agricultural land use from Idaho's Eastern Snake River Plain Aquifer area. Results indicate that 1-unit increase in irrigation percentage leads to ~US$18/ha increase in crop r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…This result reflects farmers’ adaptive behavior in response to seasonal drought by switching from water-intensive crops to drought-tolerant crops. This finding is consistent with a recent study by Xu and Li (2016), who found farmers changed their water allocation in response to water supply variations in the US west.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This result reflects farmers’ adaptive behavior in response to seasonal drought by switching from water-intensive crops to drought-tolerant crops. This finding is consistent with a recent study by Xu and Li (2016), who found farmers changed their water allocation in response to water supply variations in the US west.…”
Section: Resultssupporting
confidence: 93%
“…Modeling grain supply, demand, and trade is critical to addressing both direct and indirect effects of climate change on China’s grain production. This is particularly relevant to farmers’ micro-level adaptation practices and the subsequent changes in cropping pattern at an aggregate scale (Xu and Li, 2016). Some studies have applied equilibrium models such as the China-world Agricultural Regional Market Equilibrium Model to project Chinese grain supply and demand equilibrium change in the future based on the population, resources, economy and other factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…At times of water shortage, water right seniority guarantees an advantage to receive water from the BOR over juniors, implying more secured water supplies. Senior water right holders can irrigate more acreage of land and are less likely to have curtailed allotment while junior holders tend to predominantly bear the costs of water scarcity (Brent, 2017; Burness & Quirk, 1979; Li et al., 2017, 2019; Libecap, 2011; Schlenker et al., 2007; Xu & Li, 2016); and (2) the BOR does not require interest on project cost repayment and it subsidizes agricultural water costs by charging irrigators according to their “ability to pay.” The BOR's interest and ability‐to‐pay subsidy rates, in tandem, equaled 82% of project costs in 1975 (Moore, 1999). A variable for the average cost of surface water is used to represent surface water price.…”
Section: Empirical Modelmentioning
confidence: 99%
“…Water allocation is considered to be a key water planning method for irrigated agriculture lands and public open spaces in various parts of the world (Singh, 2015;Xu and Li, 2015;Young, 2013). Governments and water regulatory authorities often establish the amount of water allocated, however apportioning the annual allocation is generally the decision of the land manager.…”
Section: Introductionmentioning
confidence: 99%